Securing the Communist State : the Reconstruction of Coercive Institutions in the Soviet Zone of Germany and Romania, 1944-1948. - Liesbeth, van (Lexington Books, 2011)
In Securing the Communist State, Liesbeth van de Grift provides a new understanding of these organizations using recently disclosed material from the communist archives in Berlin and Bucharest. She reveals how these communist p.